Taxonomic studies of two genera, Elongationa gen. nov. and Midoria Kato (Hemiptera: Cicadellidae: Ledrinae), with two new species from China - Sun, Jing; Huang, Weijian; Zhang, Yalin (Zootaxa, 2017)
Elongationa gen. nov., a new leafhopper genus (Hemiptera: Cicadellidae: Ledrinae) with one new species, E. hyalina sp. nov., is described and illustrated in detail. A checklist and key to species in the genus Midoria are provided including a new species, Midoria curvidentata sp. nov., described in this paper.